The Impact of Captain Jonathan Carver's Maps and Journal on the 1782–1783 British-American Peace Agreement. Issue Volume 69:Issues 2(2017) (3rd July 2017) - Ahrens, M. O.
ABSTRACT: The Preliminary Articles of Peace signed in Paris on 30 November 1782 brought the American Revolutionary War to a close and defined the external limits of the United States of America. During negotiations, manuscript red boundary lines were added to the northwestern parts of at least two editions of John Mitchell's 1755 map of North America. These red lines illuminate how Captain Jonathan Carver's cartography and journal influenced the peace proceedings. Knowledge of Carver's achievements in the northern Mississippi valley and western Great Lakes region gave the American commissioners a negotiating advantage and a more complete understanding of their 'water line' boundary and vast hinterland extending northwest of Lake Superior.